Desenvolvimento e produtividade do milho (Zea mays L.) em resposta ao uso de plantas de cobertura morta - Azevedo, Marianne Costa de (2021)
Despite the importance of corn for the state of Paraíba, the state has low productivity of this grain, due to environmental and technological factors. The use of cover crops can result in increased crop productivity due to the benefits that this management brings to the soil and the main crop. The objective of this work was to evaluate the effects of the use of cover crops on agronomic characteristics, yield components and corn yield. The experiment was carried out in the Horticulture Module of the Experimental Farm Olho D'Água, CCA/UFPB, Areia-PB, for two years. Initially, cover crops (Crotalária spectabilis; Crotalaria juncea; Pigeon pea (Cajanus cajan) Millet (Pennisetum glaucum (L.) R. Br.), plus the control) were cultivated when they reached flowering. sowing of three maize genotypes (Zea mays) (AG-1051, Robusta and a creole genotype, Pontinha). The experiment was carried out in a randomized block design in split plots with four replications, where the main plot was the three corn genotypes and the secondary plots were the cover crops plus the control, totaling 72 plots. In cover crops, the green and dry mass of straw was evaluated, and in corn, stem diameter, number of leaves, plant height, yield components and yield were evaluated. Pearl millet and C. juncea were the cover crops with the highest dry matter production. The lack of mulch in the soil resulted in corn plants with smaller stem diameter and lower productivity. The Robusta maize genotype had lower plant height in all treatments. The use of cover crops did not affect ear diameter, number of rows per ear and the weight of a thousand grains of corn. The straw of C. juncea and C. spectabilis favored the increase in the weight of corn cobs. The highest corn yield is achieved when AG-1051 is cultivated in Crotalária juncea straw.